Chemical regeneration mechanism of Fe-impregnated chitosan using ferric chloride1. Issue 95 (15th October 2015) - Zhang, Jing; Chen, Nan; Feng, Chuanping; Li, Miao; Lv, Long; Hu, Qili
<x xml:space="preserve">Abstract</x> After seven regeneration/adsorption cycles, the adsorption capacity of FeCl3 regenerated Fe-CTS was 74.04 mg g−1 without significant loss in adsorption ability.